2002
DOI: 10.1603/0022-0493-95.2.414
|View full text |Cite
|
Sign up to set email alerts
|

Pro-active Management of Beet Armyworm (Lepidoptera: Noctuidae) Resistance to Tebufenozide and Methoxyfenozide: Baseline Monitoring, Risk Assessment, and Isolation of Resistance

Abstract: Susceptibility to tebufenozide and methoxyfenozide of beet armyworm [Spodoptera exigua (Hübner)] from the southern United States and Thailand was determined through exposure of first and third instars to dipped cotton leaves. Among the field populations evaluated, tebufenozide LC50 values for first and third instars, respectively, ranged from 0.377 to 4.41 and 4.37-46.6 microg (AI) /ml of solution. Methoxyfenozide LC50 values for first and third instars of field populations ranged from 0.058 to 0.487 and 0.601… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
71
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 17 publications
5
71
1
1
Order By: Relevance
“…Spindler-Barth and Spindler (1998) reported that cells of C. dilutus selected in the presence of 20E were resistant only to the moulting hormone, but still responded to tebufenozide, whereas subclones selected in the presence of tebufenozide showed cross-resistance to 20E. Related to the in vivo system, some cross-resistance has been reported between dibenzoylhydrazinetype insecticides and other insecticides in many insects (Sauphanor and Bouvier, 1995;Wearing, 1998;Waldstein et al, 1999;Moulton et al, 2002;Smirle et al, 2002;Cao and Han, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spindler-Barth and Spindler (1998) reported that cells of C. dilutus selected in the presence of 20E were resistant only to the moulting hormone, but still responded to tebufenozide, whereas subclones selected in the presence of tebufenozide showed cross-resistance to 20E. Related to the in vivo system, some cross-resistance has been reported between dibenzoylhydrazinetype insecticides and other insecticides in many insects (Sauphanor and Bouvier, 1995;Wearing, 1998;Waldstein et al, 1999;Moulton et al, 2002;Smirle et al, 2002;Cao and Han, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Methoxyfenozide and tebufenozide are the most effective of selective dibenzoylhydrazine insecticides now commercialized for the control of lepidopteran larvae. While these compounds hold promise as excellent pest control agents, some laboratory and field surveys have shown that resistance and crossresistance can evolve in response to this chemical group (Sauphanor and Bouvier, 1995;Smagghe et al, 1998Smagghe et al, , 2003Waldstein et al, 1999;Moulton et al, 2002;Gore and Adamczyk, 2004;Cao and Han, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Low levels of resistance to tebufenozide have been found in codling moth (Cydia pomonella), beet armyworm and obliquebanded leafroller populations that were not exposed to this insecticide (Moulton et al 2002;Ahmad et al 2002), suggestBecause lettuce is highly susceptible to insect damage at the seedling stage, many growers spray broad-spectrum insecticides. Some newer, more selective insecticides can bring lepidopteran pests under control without hurting their natural enemies and causing secondary pest outbreaks.…”
Section: Insecticides For Lepidopteramentioning
confidence: 99%
“…(2000) showed that the resistance of Planotortri xocto against tebufenozida increased 269 fold compared to the susceptible strain. According Moulton et al (2002), the LC 50 of metoksifenozida on field strain of Spodoptera exigua was higher than the laboratory strain (Harwanto, 2014). Resistance occur not only to conventional insecticides, but also to 3 rd generation insecticides i.e.…”
mentioning
confidence: 97%
“…pulation in the United States against emamectin benzoate vary between 1 to 6.21 fold (Moulton et al, 2002). Susceptibility of P. xylostella populations in California against emamectin benzoate were 1-13 fold .…”
mentioning
confidence: 98%